Gender and labour in times of austerity: Ireland, Italy and Portugal in comparative perspective. (19th January 2016) - ADDABBO, Tindara; BASTOS, Amélia; CASACA, Sara Falcão; DUVVURY, Nata; NÍ LÉIME, Áine
Abstract: Using Eurostat data for 2007, 2010 and 2012, the authors examine the effects of the 2008 crisis on the situation of male and female workers in Italy, Ireland and Portugal, with particular attention to changing labour market dynamics, (intra‐household) employment patterns, and incomes. The gender gaps in employment, unemployment and precarious employment are narrowing, but this trend cannot be interpreted as progress toward gender equality: it is driven by men's increasingly vulnerable position resulting from the generalized deterioration of labour market conditions, including the growth of precarious and/or low‐paid employment, unemployment and poverty to the detriment of household living standards.